Dye sensitized solar cell based on polyethylene glycol/4, 4-diphenylmethane diisocyanate copolymer quasi solid state electrolyte - Liow, Kai Sing; Coswald Stephen Sipaut @ Mohd Nasri; Rachel Fran Mansa; Jedol Dayou (Trans Tech Publications, Switzerland, 2014)
In this study, quasi-solid state electrolyte (QSE) was prepared by blending the polyethylene glycol (PEG) with molecular weight of 400, 4,4’-diphenylmethane diisocyanate (MDI), potassium iodide (KI) and iodine (I2) under a low reaction temperature (50oC) for two hours. QSEs with a different ratio of PEG to MDI were formulated. Adding 15 vol% of MDl into the QSE was found to give the highest open circuit voltage, short circuit current and energy conversion efficient, which were 360 mV, 0.077 mA/cm2 and 0.02% respectively.